Pilgrimage and Visual Genre: The Architecture of Twentieth-Century Roman Catholic Pilgrimage in Scotland. (8th August 2019) - Proctor, Robert; Gillick, Ambrose
Abstract: As Roman Catholics gained confidence in twentieth-century Scotland, they revived pre-Reformation shrines and pilgrimages and created new shrines with transnational connections to the modern Catholic world. Three sites in this campaign were Carfin, a new pilgrimage center based on Lourdes; Whithorn, site of medieval pilgrimages to Saint Ninian; and Dunfermline, associated with the canonized Queen Margaret of Scotland. Each had different meanings for Scottish Catholicism. The landscapes of these shrines included proposed new buildings, completed buildings, including shrines and churches, and existing features, notably caves or grottoes and medieval ruins. Whether found, professionally designed, or made by the clergy and their congregations, these sites framed and ordered pilgrimage rituals and lent them meaning. Seeing common architectural, visual features across these pilgrimages, and drawing on new archival research, we suggest that the employment of recognizable visual genres was a key way of creating a consensus among the faithful. International symbols of saintly presence were remade for the local context, with intertwined religious and political intentions, giving tangible expression to a revived Catholicism in Scotland, and promoting a new vision of Scotland as a Catholic nation.